Relationship between Safety Climate Factors and Safety Performance among the Workers in Cold Storage Industries - Rusli, Bin Ahmad; Chang, Li Ching; Nur Fatihah, Abdullah Bandar; Hana, Hamidi; Ahmad Sofian, Shminan; Heng, Chin Siong (American Journal of Trade and Policy (AJTP), 2018)
This study aims to determine the relationship between the safety climate factors (positive workforce safety attitude, acceptance of safety rules and regulation and reasonable production schedule) towards safety performance among workers who work under the cold storage company at Kuching, Sarawak, Malaysia. A survey methodology was used in this study. This research involves the utilization of questionnaire which was administered among one-hundred and fifty workers. The relationship between the safety climate factors (Positive workforce safety attitude, acceptance of safety rules and regulation and reasonable production schedule) were analyzed using the Pearson’s Correlation analysis test. The results of this study revealed that there is a significant relationship between (positive workforce safety attitude and acceptance of safety rules and regulation) and safety performance. Meanwhile, result showed that there is no significant relationship between reasonable production schedule and safety performance. Hence, this study hoped to raise the awareness of organization about the importance of safety climate in the workplace.